Uso de modelos simuladores como metodología docente para la carrera de Medicina - Mendoza I., Laura; Herskovic L., Pedro; Vásquez, Alicia; Quevedo R., Fernando (Revista Hospital Clínico Universidad de Chile, 2009)
Introduction: Usefulness of high tech clinical simulators as learning tools, are partially established. Objective: To determine utility of an Emergency Care Simulator (ECS) as a learning tool in medicine. Methods: Study was conducted in 2007, during the respiratory diseases rotation of third year medical students. Informed consent was required to participants. They were divided in two groups: Study Group (SG) and Control group (CG). Both were submitted to the same regular respiratory diseases learning activities. Only the SG had a session with the ECS. The simulated scenario referred to a young man with severe community pneumonia. At the end of the activities every student from those groups answered a modified essay and a questionnaire about this disease problem (maximum score was 70 points). The SG also responded a list of 12 statements to get their opinion on this experience. Results: 63 students participated in thestudy, 42 in the SG and 21 in the CG. All the SG answered the questionnaire and 31 answered the modified essay. All the CG answered the modified essay. The scores in the essay were (mean ± SD) 44, 3 ±12,9 and 35,5±14,7 for the SG and CG, respectively (p=0,026). 80% of the SG agreed that the experience was useful to learn; entertaining and allowing the application of previous knowledge. Less than 50% felt the simulation real enough. Conclusions: A learning activity about severe community acquired pneumonia with the METI ECS simulator apparently was useful for students learning and well evaluated by them.